THE SYNTAX OF THE ENGLISH DETERMINER PHRASES - Sayidov, Sardorbek (Журнал иностранных языков и лингвистики, 2023)
This paper is aimed at providing the syntax of the English determiner phrases. A determiner is called determinative is a word, phrase and affix that occurs together with a noun or noun phrase and generally serves to describe the reference of that noun or noun phrase in the context. That is a determiner may indicate whether the noun is referring to a definite or indefinite element of a class, to a closer or more distant element, to an element belonging to a specified people or thing, to a particular number or quantity. Words and phrases can be formed by both their syntactic category and their syntactic function In the phrase the dog bit the man, for example, the dog belongs to the syntactic category of noun phrase and performs the syntactic function of subject. The distinction between category and function is at the main part of a terminological issue surrounding the word determiner and various grammars have used the word to describe a category, a function, or both. Thus, there are competing analyses concerning heads and dependents in nominal groups. Also, current research coveys itself the role of the syntax determiner, determiner phrases and analyzing certain types of the English phrases and its results.